A holistic approach in understanding the effects of dietary protein sources on the growth and reproductive development of farmed abalone, Haliotis midae - Wu, Yu (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2020)
The combination of fishmeal and soya in the formulated feed of farmed South African abalone, Haliotis midae, not only improved abalone growth, but also the sustainability of the compound diets by reducing the reliance on fishmeal. However, the presence of soya produced larger gonads compared to those of abalone fed kelp or single-source protein diets. There is an increasing drive to control sexual maturation and reduce undesirable spawning events in farmed abalone. However, the reasons for the reported effects of soya inclusion on the reproductive development of farmed H. midae remain unresolved. The aim of this research was to use a combination of techniques to contribute to the understanding of the relationship between growth, reproductive and nutritional physiology of farmed H. midae fed diets of varying protein sources. These techniques included stable isotope analysis (SIA), fatty acid analysis, gonad histological assessments and haemolymph sexsteroid hormone analysis. The objectives were to examine the allocation of protein and nutritional components to somatic and reproductive tissues. This study also included the first attempt to investigate the role that sex steroid hormones play during gametogenesis. Abalone (40 "“ 50 g abalone-1) were fed one of four diets: either a single-source protein-based diet, i.e., (1) fishmeal-only (FM) or (2) soya-only (S), or a combination diet of (3) fishmeal-soya (FM S) or (4) fishmeal-sunflower meal (FM SM). Sampling occurred in 45-day intervals over one year. Dietary protein source had an effect on the growth of abalone, with enhancements in growth linked to the combination of fishmeal and a plant-protein source. The fishmeal ingredient was the most utilised protein source throughout the temporal changes in protein allocation into somatic and reproductive tissue, followed by soya and then sunflower meal. The mean whole- body mass of abalone was significantly influenced by an interaction between time and dietary treatment, with average whole-body mass changing differently over time between treatments (RM-ANOVA, F(24, 96) = 2.13, p = 0.005). Overall, abalone that were fed FM S had higher mean whole-body mass values than abalone that were fed the single-protein based diets, while abalone that were fed FM SM were similar to animals from all dietary treatments (RMANOVA, F(3, 12) = 5.75, p = 0.01). Male abalone had significantly higher gonad bulk index (GBI) values compared to females (RM-ANOVA, F(1, 24) = 49.03, p < 0.001) and this was independent of dietary treatment. Within each sex, female abalone fed the FM S diet (15.92 Â± 1.88 mm3 g-1) had significantly higher GBI values than abalone fed S (9.76 Â± 1.08 mm3 g-1), while abalone fed FM (11.96 Â± 1.71 mm3 g-1) and FM SM (11.90 Â± 0.80 mm3 g-1) were similar to abalone from all other dietary treatments (Tukey's HSD, p < 0.05). Male abalone fed the FM S (21.59 Â± 2.10 mm3 g-1) and FM SM diet (19.30 Â± 2.63 mm3 g-1) had similar GBI values and they were significantly higher than in abalone fed the S diet (14.74 Â± 1.27 mm3 g-1), while abalone fed FM S had significantly higher GBI values than abalone that consumed the FM diet (15.08 Â±1.63mm3 g-1) ( Tukey's HSD, p < 0.05). Although sunflower meal was poorly utilised, it produced similar overall growth to abalone that were fed the FM S diets. Yet, feed conversion ratio values were significantly lower for abalone fed FM S (1.30 Â± 0.13) compared to those in the other three treatments, with ratios ranging from 1.65 "“ 1.72 over the one-year. The fatty acid compositions of the somatic and gonadal tissues were similar between treatments (PERMANOVA, p = 0.21), while fatty acid composition was influenced by sampling day, tissue type and abalone sex (PERMANOVA, p < 0.05). The essential fatty acids (EFAs) eicosadienoic acid and a-linolenic acid were present in abalone tissue, but they were not detected in the diets, suggesting the important role that an alternate food source (e.g. farmed abalone also had access to diatoms) may have played and the ability that H. midae may have in converting long-chain polyunsaturated fatty acids from C18 precursors. A change in the abundance of EFAs in the gonad tissue during highest and lowest GBI values suggested that arachidonic, eicosapentaenoic, g-linolenic and linoleic acid were important in females, while eicosapentaenoic, eicosadienoic and a-linolenic acid were important for male reproductive development. Dietary protein sources had an effect on the frequency distribution of maturity stages, where females that were fed FM S produced more ripe gonads and more males that were fed FM SM contained testes that showed signs of ripeness over the one-year study. Although dietary protein influenced the sex steroid concentrations in females and males, exhibiting fluctuations throughout the one-year period, no distinct pattern linked to gametogenesis were observed. The results from this study illustrate: (1) the importance of conducting laboratory studies when implementing SIA and mixing models in aquaculture nutrition; (2) conducting nutritional studies on mature, grow-out abalone; and (3) assessing the importance of naturally occurring diatoms in their diet and their contribution to growth and reproduction. The novel contribution of this research towards abalone nutritional physiology, the implications of these findings to industry as well as potential considerations for future studies were addressed.
Keywords: Abalones -- Nutrition; Abalones -- Reproduction; Abalones -- Growth; Abalone culture; Haliotis midae -- Nutrition; Haliotis midae -- Reproduction; Haliotis midae -- Growth; Haliotis midae fisheries